The influence of early diet quality on the mental health of college students: the mediation effects of height and qi-deficiency - Wang, Xinzhu; He, Xinyu; Fu, Kaixian; Zhang, Yuxia (Frontiers in Public Health, 2024)
Background In China, the prevalence of mental health issues among college students is a significant concern in society. This study aims to investigate the impact of early dietary quality on the psychological well-being of college students and elucidate the underlying mechanisms through which these effects occur, specifically focusing on height and qi-deficiency as mediators according to Chinese traditional medicine (CTM). Methods A total of 655 college students were surveyed in October 2023 using paper-pencil-based questionnaires at four second-tier universities in Sichuan Province. The assessment included mental health, height, and qi-deficiency. Pearson’s correlation and linear regression analyses were employed to examine the mediation model and test the hypotheses. Results The college students exhibited acceptable levels of early diet quality (M = 3.72) and mental health (M = 3.63), while also presenting mild qi-deficiency symptoms (M = 2.25). Their average height was measured at 164.61 cm. Early diet quality demonstrated significant associations with mental health (r = 0.38, p < 0.01), height (r = 0.32, p < 0.01), and qi-deficiency (r = −0.32, p < 0.01). Mental health displayed correlations with height (r = 0.32, p < 0.01) and qi-deficiency (r = −0.49, p < 0.01). The results of linear regression analyses revealed significant associations between early diet quality and mental health (β = 0.31, p < 0.01), height (β = 0.21, p < 0.01), as well as qi-deficiency (β = −0.26, p < 0.01). Furthermore, when early diet quality was included in the regression model, both height (β = 0.21, p < 0.01) and qi-deficiency (β = −0.35, p < 0.01) emerged as significant mediators in the relationship with mental health. Conclusion The mediation model and hypotheses were strongly supported, demonstrating that early diet quality exerted an influence on the mental health of college students through two distinct pathways: height and qi-deficiency. Moreover, the mediating effect of qi-deficiency was found to be more pronounced than that of height in the relationship between early diet quality and mental health among college students.